EKSISTENSI BANTUAN HUKUM KEPADA TERSANGKA TERHADAP PELANGGARAN HAM YANG DILAKUKAN POLISI - Salfutra, Reko Dwi (LPPM Universitas Bina Insan, 2020)
Legal aid is an institution that supports juridical support for law enforcement agreements, mostly in order to accompany justice seekers in fighting for rights. The method of choosing normative law because it discusses the rules of invitation, literature, and journals as well as papers relating to the material examined, which consists of the type of data obtained in this study is secondary data that is data obtained from library research and documentation, which is the result of research and the processing of other people, which are already available in the form of literature or documentation in this legal aid, there is a collection of experts or legal experts related to their expertise, legal issues relating to someone involved in the problem or seek help, can be used or fought for. The phenomenon of seizing human rights perpetrated by the police during arrests and checks is still common. The closest police officer filed a lawsuit against violations, the police only evaded, committed acts of self-defense or prevented the suspect from escaping.